Study Epidemiologi Dengan Pendekatan Analisis Spasial Temporal Pada Kejadian Demam Berdarah Dengue (DBD) Di Kecamatan Masaran Kabupaten Sragen Tahun 2016-2018 - Dodiet Aditya Setyawan (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: The high number of visits by sufferers of some environmental-based diseases to health service centers shows that the disease is still a serious problem in Indonesia, and one of them is Dengue Hemorrhagic Fever (DHF). Dengue Hemorrhagic Fever (DHF) in Sragen regency has become endemic, especially in the Masaran sub-district reportedly still an endemic area of ​​dengue fever. Geographically, the endemicity of Dengue Hemorrhagic Fever (DHF) in an area can be described using Geographic Information Systems (GIS). Research Objectives: This study aims to provide an overview of the Spatial and Temporal Dengue Hemorrhagic Fever (DHF) distribution based on population density and rainfall factors as well as to provide a description of the endemicity of the area against DHF in Masaran District, Sragen Regency with the application of Geographic Information Systems (GIS). Methods: The design of this study was Observational Analytic with Crossectional approach using Geographic Information Systems (GIS) modeling. The data used are secondary data about the incidence of DHF from the Sragen District Health Office in 2016-2018. The research subjects were determined by a Registry Based Study approach with a saturated sampling technique. The collected data will be analyzed descriptively by displaying a frequency distribution table, bivariate analysis with the Pearson Product Moment test and spatial-temporal analysis using the Geographic Information System (GIS) function. Results: The results of this study indicate that the spatial distribution of Dengue Hemorrhagic Fever (DHF) events is distributed randomly to all regions in Masaran District, Regency. The incidence of DHF in Masaran Subdistrict, Sragen Regency was related to Rainfall (p = 0.006) with a negative correlation direction (r = -0.741). The incidence of DHF in The Masaran Subdistrict, Sragen Regency was not related to population density (p = 0.839). Spatially-Temporal shows that there are 6 Villages in Masaran Subdistrict, Sragen Regency which are endemic areas of Dengue Hemorrhagic Fever (DBD), namely Sepat, Dawungan, Masaran, Jati, Pringanom and Krikilan villages. Conclusion: Incidence of Dengue Hemorrhagic Fever (DHF) in Masaran Subdistrict, Sragen Regency is related to Rainfall, where low rainfall tends to increase the incidence of DHF. During 2016-2018 in Masaran Subdistrict, Sragen Regency, there were 6 villages which were endemic areas of DHF, namely Sepat, Dawungan, Masaran, Jati, Pringanom and Krikilan villages.